2021 Creeping Bentgrass Putting Green National Turfgrass Evaluation Program Trial - Dani McFadden; Jack D. Fry (Kansas Agricultural Experiment Station Research Reports, 2022)
Creeping bentgrass (Agrostis stoloniferaL.) is the most common cool-season grass used for putting surfaces in Kansas and other temperate regions of the world. Fine-textured and high-density cultivars (‘Penn A-1’, ‘Penn A-2’, and ‘Penn A-4’) released in the late 1990s are widely accepted throughout the transition zone. However, new cultivars with attractive characteristics continue to be selected, evaluated, and introduced to determine their long-term suitability for Kansas.
Keywords: bentgrass; putting green; National Turfgrass Evaluation Program; NTEP